Disentangling the Impact of Catchment Heterogeneity on Nitrate Export Dynamics From Event to Long‐Term Time Scales. Issue 1 (12th January 2021) - Winter, Carolin; Lutz, Stefanie R.; Musolff, Andreas; Kumar, Rohini; Weber, Michael; Fleckenstein, Jan H.
Abstract: Defining effective measures to reduce nitrate pollution in heterogeneous mesoscale catchments remains challenging when based on concentration measurements at the outlet only. One reason for this is our limited understanding of the subcatchment contributions to nitrate export and their importance at different time scales. While upstream subcatchments often disproportionally contribute to runoff generation and in turn to nutrient export, agricultural areas (which are typically found in downstream lowlands) are known to be a major source of nitrate pollution. To examine the interplay of different subcatchments, we analyzed seasonal long‐term trends and event dynamics of nitrate concentrations, loads, and the concentration–discharge relationship in three nested catchments within the Selke catchment (456 km 2 ), Germany. The upstream subcatchments (40.4% of total catchment area, 34.5% of N input) had short transit times and dynamic concentration–discharge relationships with elevated nitrate concentrations during wet seasons and events. Consequently, the upstream subcatchments dominated nitrate export during high flow and disproportionally contributed to overall annual nitrate loads at the outlet (64.2%). The downstream subcatchment was characterized by higher N input, longer transit times, and relatively constant nitrate concentrations between seasons, dominating nitrate export during low‐flow periods. Neglecting the disproportional role of upstream subcatchments for temporally elevated nitrate concentrations and net annual loads can lead to an overestimation of the role of agricultural lowlands. Nonetheless, constantly high concentrations from nitrate legacies pose a long‐term threat to water quality in agricultural lowlands. This knowledge is crucial for an effective and site‐specific water quality management. Plain Language Summary: To efficiently remove nitrate pollution, we need to understand how it is transported, mobilized, and stored within large and heterogeneous catchments. Previous studies have shown that upstream catchments often have a disproportional impact on nutrient export, while agriculture (a major nitrate source) is often located in downstream lowlands. To understand which parts of a catchment contribute most to nitrate export and when, we analyzed long‐term (1983–2016) and high‐frequency (2010–2016) data in the Selke catchment (Germany) at three locations. The mountainous upstream part dominated nitrate transport during winter, spring, and rain events. It had a surprisingly high contribution to annual nitrate loads. The agricultural downstream part of the catchment dominated nitrate export during summer and autumn, with relatively constant concentrations between seasons. Here, nitrogen inputs needed more than a decade to travel through the subsurface of the catchment, which causes a time lag between measures to reduce nitrate pollution and their measurable effect. The resulting storage of nitrate in the groundwater threatens drinking water quality for decades to come. While the role of agricultural lowlands for nitrate export can be overestimated if neglecting the disproportional role of upstream subcatchments, their impact poses a long‐term threat to water quality. Key Points: Analyzing the CQ relationship across time scales allows the disentanglement of the impact of catchment heterogeneity on nitrate export Mountainous upstream subcatchments can dominate nitrate export during high flows and disproportionally contribute to nitrate loads Agricultural downstream subcatchments can dominate nitrate export during low flow and pose a long‐term threat to water quality